2003
DOI: 10.1002/ajmg.a.20489
|View full text |Cite
|
Sign up to set email alerts
|

Does chromosome 22 have anything to do with sex determination: Further studies on a 46,XX,22q11.2 del male

Abstract: Several years ago, we presented a patient with true hermaphroditism and partial duplication of chromosome 22 and no evidence of SRY (Aleck et al. [1999: Am J Med Genet 85:2-4]). Recently a 46,XX male with velocardiofacial syndrome and a deletion of 22q11.2 and no evidence of Y chromosomal loci in blood DNA was reported (Phelan et al. [2003: Am J Med Genet 116A:77-79]). We have restudied this patient as he enters puberty. Because chromosomal deletions sometimes involve micro rearrangements of nearby material, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In 2003, the same group reported on another patient with an XX male phenotype and a typical 22q11.2 deletion. The authors concluded that the deletion and sex reversal phenotypes may have co‐occurred in the same individual by chance, given the high frequency of the typical 22q11.2 deletion (Erickson et al, ). Polanco et al () using a transgenic mouse approach, tested the hypothesis that Sox10 overexpression causes XX sex reversal, proposing that human SOX10 is involved in 22q duplication 46,XX male syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the same group reported on another patient with an XX male phenotype and a typical 22q11.2 deletion. The authors concluded that the deletion and sex reversal phenotypes may have co‐occurred in the same individual by chance, given the high frequency of the typical 22q11.2 deletion (Erickson et al, ). Polanco et al () using a transgenic mouse approach, tested the hypothesis that Sox10 overexpression causes XX sex reversal, proposing that human SOX10 is involved in 22q duplication 46,XX male syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…This deletion may provide a partial explanation of the VSD in Patient 2 with haploinsufficiency for CRKL (within the deleted segment) suggested as a candidate gene responsible for the CHD in these patients [Breckpot et al, ]. 46,XY gonadal dysgenesis has not been reported in these patients, but two patients have been reported with 46,XX testicular DSD who were found to have the DiGeorge deletion [Phelan et al, ; Erickson et al, ]. Similar to the presence of the 45,X cell line, this deletion makes assigning responsibility to any one causative cytogenetic aberration difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The gene responsible for this DSD phenotype is still unknown, but EMX2 has been suggested to be a likely candidate (Ogata et al 2000). Deletions and duplications of chromosome 22q11.2 have been identified in three cases of 46,XX testicular DSD (which were SRY -negative) (Aleck et al 1999; Erickson et al 2003; Seeherunvong et al 2004). The causative gene(s) haven't been identified, but this region contains the MAPK1 gene, which appears to play an important role in proper testis development.…”
Section: Identifying Novel Genes In the Sex Determining Pathwaymentioning
confidence: 99%